Corrigendum: Women, Wealth, and Mobility - Edlund, Lena; Kopczuk, Wojciech (American Economic Review, 2009)
* Edlund: Department of Economics, Columbia University, 420 W 118th Street, New York, NY 10027 (e-mail: le93@columbia.edu); Kopczuk: Department of Economics and SIPA, Columbia University, 420 W 118th Street, New York, NY 10027 (e-mail: wk2110@columbia.edu). We have benefited from comments by Douglas Almond, Boyan Jovanovic, Aloysius Siow, the editor, numerous anonymous referees, and seminar participants at the University of Massachusetts at Amherst, Dartmouth University, and the 2006 ASSA meeting. Barry Johnson helped us in obtaining tabulations from the IRS estate tax returns. Emmanuel Saez provided the electronic version of Forbes data. The exposition of the paper has been greatly improved by the anonymous referees’ suggestions and Merriol Baring-Gould’s text editing. Financial support from the Program for Economic Research at Columbia University, the Sloan Foundation, and National Science Foundation grant SES-0617737 is gratefully acknowledged. 193